"In vitro" correction of the severe factor V deficiency‐related coagulopathy by a novel plasma‐derived factor V concentrate. Issue 4 (26th March 2018) - Bulato, C.; Novembrino, C.; Anzoletti, M. Boscolo; Spiezia, L.; Gavasso, S.; Berbenni, C.; Tagariello, G.; Farina, C.; Nardini, I.; Campello, E.; Peyvandi, F.; Simioni, P.
Abstract : Introduction: Severe congenital factor V (FV) deficiency is a rare bleeding disorder characterized by very low/undetectable levels of FV. Fresh frozen plasma is the standard treatment for bleeding manifestations. Recently, a novel plasma‐derived FV concentrate has been developed. Aim: To evaluate the "in vitro" ability of the novel FV concentrate to normalize clotting times and generate normal amount of thrombin in plasma collected from patients with severe FV deficiency. Methods: Prothrombin time (PT), activated partial thromboplastin time (aPTT), FV activity and antigen levels and thrombin generation were measured pre‐ and postspiking of plasma samples of 10 patients with increasing doses of FV concentrate (from 0 to 100 IU/dL). Results: Prothrombin time and activated partial thromboplastin time ratios as well as all thrombin generation parameters were fully corrected by the addition of FV concentrate at a final concentration of 25 IU/dL. However, the addition of FV at a concentration of 1‐3 IU/dL was already sufficient to correct peak height and endogenous thrombin potential (but not lag time and time to peak) after activation with 5 pmol/L tissue factor. FV activity and antigen levels showed a linear response to supplementation with the novel FV concentrate. Conclusion: The novel plasma‐derived FV concentrate was effective to correct "in vitro " severe FV deficiency in patients. The optimal FV concentration to fully normalize both global clotting times and thrombin generation parameters using the novel plasma‐derived FV concentrate was 25 IU/dL.